Use of good patient safety practices in the perioperative period: attitudes of the nursing team - Silva, Ludimila Alves da (2023)
In Brazil, the latest bulletin on patient safety and quality in health services, published by ANVISA in 2020, pointed out that in 2018, 4,812 incidents occurred in the HS capable of resulting in serious outcomes for the patient were reported. The nursing category, as the largest workforce of hospital organizations, has a strong influence on patient safety, and can collaborate with practices that qualify care and ensure the best possible outcomes for the patient. To identify in the scientific literature actions/attitudes of the nursing team related to patient safety in the perioperative period. This is an integrative literature review conducted in August and September 2022, searching the scientific databases Scientific Electronic Library Online (SCIELO) and the Virtual Health Library (VHL) collection. We identified n=866 publications on the topic of patient safety and perioperative nursing, of which n=43 old full-texts met the inclusion/eligibility criteria. Of these, n=15 studies were selected to compose the sample of the present review. The initiative and planning of the implementation process and/or use of safe surgery protocols and checklist were the practices that appeared in greater number in the publications, followed by effective communication and development of permanent and continuing education actions for patient safety. It was found that the nursing team uses good patient safety practices in the perioperative period, but several challenges limit its effective implementation.